Endoscopy in Inflammatory Bowel Diseases: From Proven to New Endoskopie bei chronisch entzündlichen Darmerkrankungen: Neues und Bewährtes - Rath, Timo; Neurath, Markus (Deutsche Medizinische Wochenschrift, 2025)
Inflammatory bowel diseases with the 2 main forms - ulcerative colitis and Crohn's disease - are chronic relapsing diseases of the gastrointestinal tract in which dysregulation of the intestinal immune system against commensal components of the microbiome leads to perpetuated intestinal inflammation based on a genetic predisposition. While in the past symptom control was the focus of therapy, more recent data show that achieving endoscopic remission is superior to sole clinical symptom control for the further course and prognosis of the diseases. In this review article, we will present the significance of endoscopy for inflammatory bowel diseases, describe established scoring systems for endoscopic graduation of inflammatory activity and, last but not least, also present and review new endoscopic developments.
CRIS-Team Scopus Importer:2025-05-30
Keywords: colonoscopy; confocal laser endomicroscopy; Crohn's disease; endocytoscopy; endoscopy; inflammatory bowel diseases; ulcerative Colitis